Curcumin-Mediated Degradation of S-Phase Kinase Protein 2 Induces Cytotoxic Effects in Human Papillomavirus-Positive and Negative Squamous Carcinoma Cells - Khan, Abdul Q.; Siveen, Kodappully S.; Prabhu, Kirti S.; Kuttikrishnan, Shilpa; Akhtar, Sabah; Shaar, Abdullah; Raza, Afsheen; Mraiche, Fatima; Dermime, Said; Uddin, Shahab (Frontiers in Oncology, 2018)
S-phase kinase-associated protein2 (Skp2), a proto-oncoprotein, plays an important role in development and progression of human malignancies. Skp2 is frequently overexpressed in many human malignancies. It targets cell cycle progression through ubiquitin mediated degradation of G1-checkpoint CDK inhibitors—p21 (CDKN1A) and p27 (CDKN1B). We investigated the role of Skp2 and its ubiquitin-proteasome pathway in head and neck squamous cell carcinoma (HNSCC) using a panel of cell lines with and without human papillomavirus (HPV+, HPV−). Treatment of HNSCC cell lines with curcumin, a natural compound isolated from rhizomes of the plant Curcuma longa, or transfection of small interfering RNA of Skp2, causes down-regulation of Skp2 with concomitant accumulation of p21 and p27 in HPV+, HPV− cells. Furthermore curcumin inhibits cell viability and induces apoptosis in a dose-dependent manner. Treatment of HPV+ and HPV− cells with curcumin induced apoptosis via mitochondrial pathway and activation of caspases. In addition, treatment of HPV+ and HPV− cell lines with curcumin down-regulated the expression of XIAP, cIAP1, and cIAP2. Interestingly, co-treatment of HNSCC cells with curcumin and cisplatin potentiated inhibition of cell viability and apoptotic effects. Altogether, these data suggest an important function for curcumin, acting as a suppressor of oncoprotein Skp2 in squamous cell carcinoma cells in both HPV+ and HPV− cells; raise the possibility that this agent may have a future therapeutic role in squamous cell carcinoma.